The Impact of Biofeedback on Diabetic Patients' Glycemia - Fariba Aaraji; Masoud Nosratabadi; Mohammadjavad Hoseinpourfard (Baqiyatallah University of Medical Sciences, 2018)
Background: Complementary medicine claims that biofeedback affects the reduction of blood glycemia. Objective: The current study aimed to determine the effects of biofeedback on decreasing blood glucose levels and tension and increasing the quality of life in diabetic patients. Methods: The current retrospective evidence-based study used pretest-posttest accidental sampling to select a group of 30 diabetic patients admitted to Glenview Clinic in the Aghdasiyeh region, Tehran, Iran, as the sample. Participants were divided into two 15-membered groups, the experiment and the control groups, matched by age and gender. Data gathering tools included the Quality of Life questionnaire in diabetic patients by Thomas et al, the Perceived Tension Index by Cohen et al, a glucometer, and the fasting blood glucose test. Data was analyzed using analysis of covariance (ANCOVA). Results: The results showed that biofeedback training was effective in decreasing blood glucose levels in diabetic patients. Conclusion: Biofeedback can reduce tension and improve the quality of life of diabetic patients; thus, it could be used as a complementary service in healthcare centers.